Knowledge of Disaster Risk and Perceptions of Climate Change among College Students - Muttaqin, Islakhul; Febriani, Prita (Universitas Negeri Surabaya, 2024)
Indonesia is on the path of the Pacific Ring of Fire so all regions in Indonesia are prone to disasters. The last ten years have also seen many disasters in several areas. The reason is climate change which has an impact on erratic weather. This study aims to determine the effect of knowledge of disaster risk on perceptions of climate change in college students. Quantitative research method with 101 student subjects. The measurement tools used are disaster risk knowledge and climate change perceptions. The results of the study show that there is a relationship between knowledge of disaster risk and perceptions of climate change among college students. The effective contribution shows 39.3%, meaning that disaster risk knowledge contributes 39.3% to climate change perceptions, and 69.7% is influenced by other factors. The results also show that students' knowledge of disaster risk is low and students' perceptions of climate change are negative. The results of this study are important as a basis for making interventions in the form of more effective and massive education for students about disaster risk.